Bio-energy conversion performance, biodegradability, and kinetic analysis of different fruit residues during discontinuous anaerobic digestion - Zhao, Chen (Waste management (New York, N.Y.), 2016)
Copyright © 2016 Elsevier Ltd. All rights reserved.